Inter-comparison of long-term wave power potential in the Black Sea based on the SWAN wave model forced with two different wind fields - Islek, Fulya; Yuksel, Yalcin (ELSEVIER, 2021)
In this study, a long-term comparative assessment of the potential of wave power in the Black Sea was conducted using the calibrated and validated SWAN (Simulating WAves Nearshore) model forced by two well-known wind fields. The European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim and National Centers for Environmental Prediction/Climate Forecast System Reanalysis (NCEP/CFSR) wind fields were used, covering data from 1979 to 2018. In general, the wave power potential based on the results of the CFSR wind field was found to be slightly higher than that obtained with the ERA-Interim wind field. The greatest discrepancy between the results of the ERA-Interim and CFSR wind fields was observed in the northeastern Black Sea. The spatial distributions of the wave power were also evaluated on a seasonal scale using wave parameters obtained from the calibrated SWAN model. The wave climate obtained from both long-term and seasonal assessments indicates that the western Black Sea, especially the southwestern Black Sea, is characterized by higher wave power potential and lower variability, while the eastern Black Sea has lower wave power potential and higher variability. Stable and powerful long-term wave conditions in the southwestern Black Sea can indicate that this region is a suitable location for wave farms. In contrast, the effect of the long-term variability on wave power is greatest in the eastern Black Sea owing to the highly variable wave conditions in this region.
Keywords: Renewable energy; Wave energy potential; Long-term assessment; SWAN model; Black Sea; ENERGY-RESOURCES; HINDCAST; CLIMATE; OCEAN; Geochemistry & Geophysics; Meteorology & Atmospheric Sciences; Oceanography